Late Quaternary glacial advances in the Tons River Valley, Garhwal Himalaya, India and regional synchronicity. (October 2014) - Mehta, Manish; Dobhal, DP; Pratap, Bhanu; Majeed, Zahid; Gupta, Anil K; Srivastava, Pradeep
The glacial history of the Tons River Valley reveals significant changes in the glacier extent during the late Quaternary driven by regional and global climatic changes. The successions of moraines in glaciated valley of the upper Tons River, Garhwal Himalaya, provide evidence of at least five glacial advances during the late Quaternary Period. This study discusses about the synchronicity of Himalayan glaciers and comparison between results of Optically Stimulated Luminescence (OSL) and Cosmogenic Radio Nuclide (CRN 10 Be) dates. The OSL dates of moraine sediments deposited by glacier in the upper Tons valley show parallelism with the ages deduced from the CRN of 10 Be by Scherler et al. in the same area. The five episodes of glacier advances are dated at 20 ± 3, 16 ± 2, 8 ± 1.2, 6 ± 0.7 and 3 ± 0.6 kyr (between Marine Isotope Stages (MISs) I and II). Two of the more extensive phases of glaciation were during the early and later parts of MIS II, which attributed to the lower temperature and enhanced the mid-latitude westerlies. During the periods between 20 ± 3 kyr and present day, the glacier lost ~47 km 2 (33%) area, 0.88 × 10 10  m 3 water equivalent (w.e.) volume with the rate of 0.44 × 10 6  m 3 w.e./yr, which is close to the current melting rates of Central Himalayan glaciers. The estimation of equilibrium line altitude (ELA) using these dates and geomorphic data suggests a vertical shift of ~451 m for Jaundhar Glacier and ~598 m for Bandarpunch Glacier since 20 kyr. The results from Tons valley glaciation show synchronicity with the records of glacial advancements from the other Himalayan glacier valleys. These data allow testing of two widely used dating techniques and importance of global climate change and monsoon influence on glaciation in the Himalaya.